Micro and Nano Fabrication Tools and Processes - Gatzen, Hans H. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
For Microelectromechanical Systems (MEMS) and Nanoelectromechanical Systems (NEMS) production, each product requires a unique process technology. This book provides a comprehensive insight into the tools necessary for fabricating MEMS/NEMS and the process technologies applied. Besides, it describes enabling technologies which are necessary for a successful production, i.e., wafer planarization and bonding, as well as contamination control.